Penerapan terapi suportif dengan teknik bimbingan untuk mengurangi dorongan bunuh diri pada pasien skizofrenia - Sulastry Pardede (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2017)
This research investigated a paranoid type of schizophrenia patients who have a high suicide impulse is characterized by depression and mental disorders, desperate and feel helpless, negative events in life, social isolation, family disorders, lack of understanding of the meaning of life and negative self-acceptance. The purpose of this study was to determine the clinical features and application of supportive therapy with counseling techniques to reduce impulse suicide in schizophrenic patients. The method used in this study is a single case study design. Researcher using observation, interviews and psychological tests which are Wechsler-Bellevue Intelligence Scale (WBIS), Sack’s Sentence Completion Test (SSCT), Graphics, Minnesota Multiphasic Personality Inventory (MMPI) and supportive therapy intervention with counseling techniques. Results showed reduced impetus suicide intervention, strengthened by the results of pre-test 9 in medium category (medium Intent), while the post-test scores are included into the low category 3 (low intent) with the Suicide Intent Scale (SIS). Prognosis on the subject: positive, where the impulse suicide reduced.